Co-delivery of nigericin and decitabine using hexahistidine-metal nanocarriers for pyroptosis-induced immunotherapeutics - Qiang Niu; Yu Liu; Yujing Zheng; Ziwei Tang; Yuna Qian; Ruogu Qi; Jianliang Shen; Ping Zhao (Elsevier, 2022)
Pyroptosis provides a new window for relieving the tumor immunosuppressive microenvironment (TIM) and promoting systemic immune responses for tumor treatments. However, gasdermin D (GSDMD), a key protein in the pyroptosis process mediated by caspase-1, is low expressed in the majority of tumor cells and small-molecule inhibitors of DNA methylation suffer from nonspecific or single-function defects. To address these issues, hexahistidine (His6)-metal assembly (HmA) was employed as the drug delivery vector to load nigericin (Nig) and decitabine (DAC) affording a dual-drug delivery system (Nig + DAC)@HmA. The (Nig + DAC)@HmA nanoparticles are efficiently internalized by cells through endocytosis, easily escape from the lysosome, and are highly distributed in the tumor sites. DAC up-regulates the expression of GSDMD which is then cleaved by the nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) inflammasome and caspase-1 protein activated by Nig. Effective cancer cell pyroptosis is thus achieved and induces a significant systemic antitumor immunity for impressive tumor suppression with negligible side effects in vivo. Our results suggest that such an easy-to-manipulate self-assembled nano-system (Nig + DAC)@HmA provides a new anticancer path by enhancing pyroptosis through reinforced inflammation.